Meningkatkan Keaktifan Belajar Siswa Kelas V SDQT Nurul Islam dengan Metode Kooperatif Group Investigation - Hadi, Firda Rahmadina; Aisyah, Siti; Gustian, Rafi Dwi; Farida, Nur Aini; Makbul, M. (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study is to increase students learning activties by applying the cooperative learning model Group Investigation model. The research method in this study was carried out by applying the cooperative learning model of the Group Investigation model to improve student learning activties and was carried out in Class V SDQT Nurul Islam in Karawang City. The results showed that the learning activty of Class V students of SDQT Nurul Islam with the Cooperative Method increased from cycle I to cycle II by 17%. In the first cycle, the classical average of student learning activty was 73% and included in the Good category. While in cycle II, the classical average of student learning activty increased quite significantly, namely to 90% and included in the Very Good category. It can be concluded that the application of the cooperative learning model of the Gr model.